Lisvane's Legacy? Constitutional reform in the Isle of Man. (March 2020) - Edge, Peter W
Abstract: The Isle of Man is a largely autonomous dependent territory of the UK. In 2016, Lord Lisvane was commissioned to report on the functioning of the principal organ of governance, the Tynwald. This Lisvane Review has led to substantial constitutional reform within this small democracy, particularly in relation to the unelected second chamber of Tynwald, the Legislative Council. This reflects an ancient tension within the Manx constitution between the House of Keys, since the mid-nineteenth century a directly elected chamber, and the unelected Legislative Council. The Lisvane period saw important changes to the composition and powers of the Legislative Council, as well as gender diversity within Tynwald as a whole. Placing the Manx experience within a broader small democracy theoretical and comparative framework demonstrates not only the possibility of constitutional reform, but also provides insights into resources for constitutional development, the special challenges of managing intimacy, and the dangers of over-concentration of power in a small democracy.